2014
DOI: 10.1177/0883073814527163
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Genotype in Pediatric Migraine Patients

Abstract: There is no information about the role of transforming growth factor-beta 1 (TGF-β1) in the pathogenesis of pediatric migraine. This study included 100 consecutive children and adolescents in whom migraine was diagnosed and 88 healthy children and adolescents. The isolated genomic DNA was used as a template for TGFβ-1 (-800G/A, -509C/T, 869T/C [codon 10] and 915G/C [codon 25]) genotyping. The allelic frequency of 509C/T was significantly different between control and migraine without aura patients (P = .04). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Plasma level of TGFB1 has been shown to increase in patients with migraine during headache-free periods compared to healthy subjects without headache 34 . Another study investigated the TGFB1 genotype in pediatric migraine patients and reported significant differences between control and migraine patients 35 . Our DEPICT gene analysis also prioritized JAG1 at the novel 20p12 migraine-associated locus.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma level of TGFB1 has been shown to increase in patients with migraine during headache-free periods compared to healthy subjects without headache 34 . Another study investigated the TGFB1 genotype in pediatric migraine patients and reported significant differences between control and migraine patients 35 . Our DEPICT gene analysis also prioritized JAG1 at the novel 20p12 migraine-associated locus.…”
Section: Discussionmentioning
confidence: 99%
“…The specific expression patterns of MCP-1, IL-10, TGF-beta, and other cytokines have also been linked with migraine disease development [ 37 , 38 ]. Furthermore, Saygi et al suggested that TGF-beta 1 genotypes are associated with pediatric migraine development [ 39 ]. This raises the possibility that hsa_circRNA_000367 and hsa_circRNA_102413 may modulate migraine pathogenesis via regulating the expression of these and other inflammatory factors, although further experiments will be needed to confirm this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…5 In keloids patients, TGF-β1 stimulates keloid fibroblast proliferation and collagen 12 reported that TGF-β1 levels in cerebrospinal fluid cytokines were higher in patients with migraines compared with a control group of patients without migraines. Saygi et al 13 further reported a significantly higher frequency of TGF-β1 polymorphisms in migraine patients compared with healthy controls. In Eiser, 14 TGF-β1 activation appeared to mediate morbidities associated with keloids in African-Americans.…”
Section: Risks Factors For Migraine In Keloids Groupmentioning
confidence: 94%